Convergence of congenic mapping and allele-specific alterations in tumors for the resolution of the Skts1 skin tumor susceptibility locus - de Koning, J P; Wakabayashi, Y; Nagase, H; Mao, J-H; Balmain, A (Oncogene, 2007)
Although several familial cancer genes with high-penetrance mutations have been identified, the major genetic component of susceptibility to sporadic cancers is attributable to low-penetrance alleles. These ‘weak’ tumor susceptibility genes do not segregate as single Mendelian traits and are therefore difficult to find in studies of human populations. Previously, we have proposed that a combination of germline mapping and analysis of allele-specific imbalance in tumors may be used to refine the locations of susceptibility genes using mouse models of cancer. Here, we have used linkage analysis and congenic mouse strains to map the major skin tumor susceptibility locus Skts1 within a genetic interval of 0.9 cM on proximal chromosome 7. This interval lies in an apparent recombination cold spot, and corresponds to a physical distance of about 15 Mb. We therefore, used patterns of allele-specific imbalances in tumors from backcross and congenic mice to refine the location of Skts1. We demonstrate that this single tumor modifier locus has a dramatic effect on the allelic preference for imbalance on chromosome 7, with at least 90% of tumors from the congenics showing preferential gain of markers on the chromosome carrying the susceptibility variant. Importantly, these alterations enabled us to refine the location of Skts1 at higher resolution than that attained using the congenic mice. We conclude that low-penetrance susceptibility genes can have strong effects on patterns of allele-specific somatic genetic changes in tumors, and that analysis of the directionality of these somatic events provides an important and rapid route to identification of germline genetic variants that confer increased cancer risk.